IR-Spectroscopic Study on the Interface of Cu-Based Methanol Synthesis Catalysts: Evidence for the Formation of a ZnO Overlayer - Schumann, Julia; Kröhnert, Jutta; Frei, Elias; Schlögl, Robert; Trunschke, Annette (Topics in catalysis, 2017)
Carbon monoxide was applied as probe molecule to compare the surface of a ZnO-containing (Cu/ZnO:Al) and a ZnO-free (Cu/MgO) methanol synthesis catalyst (copper content 70 atomic %) after reduction in hydrogen at 523 K by DRIFT spectroscopy. Nano-structured, mainly metallic copper was detected on the surface of the Cu/MgO catalyst. In contrast, the high energy of the main peak in the spectrum of CO adsorbed on reduced Cu/ZnO:Al (2125 cm −1 ) proves that metallic copper is largely absent on the surface of this catalyst. The band is assigned to Zn δ+ –CO. The presence of not completely reduced Cu δ+ –CO species cannot be excluded. The results are interpreted in terms of a partial coverage of the copper nano-particles in the Cu/ZnO:Al catalyst by a thin layer of metastable, defective zinc oxide. Minor contributions in the spectrum at 2090 and 2112 cm −1 due to nano-structured Cu 0 –CO and CO adsorbed on highly defective Cu 0 , respectively, indicate that the coverage of metallic copper is not complete.